The effect of combined melatonin and curcumin on sperm quality parameters, induction of apoptosis and membrane lipid peroxidation during the sperm freezing process - Maryam Zamani; Fariba Zafari; Farzad Rajaei; Amir Farzam; Zeinab Khodakarmi; Amir Hosseini (Mashhad University of Medical Sciences, 2023)
Introduction: Infertility is a disorder that affects about 15% of couples and 50% is related to male. Sperm freezing involves storing semen samples at -196°C in liquid nitrogen. During freezing, due to the induction of apoptosis through oxidative stress, the functional indicators of sperm are damaged and ultimately lead to a decrease in fertility. There have been many studies on the use of freezing environments with complementary antioxidants to limit the damage caused by freezing. In this study, melatonin and curcumin were used in combination as antioxidants in sperm freezing.Methods: This study was conducted in 2022 on the semen of 40 men with normal sperm in Qazvin University of Medical Sciences. To check sperm motility by CASA device, morphology by hematoxylin staining, viability by eosin nigrosine staining, DNA integrity by tunnel kit and MDA measurement by reaction method with thiobarbituric acid and spectrophotometer were used. Data analysis was done using SPSS software (version 25) and ANOVA test, dependent t-test and one-way analysis of variance. P<0.05 was considered statistically significant.Results: The use of melatonin and curcumin either separately or in combination in the freezing environment had a significant effect on the rate of motility and survival, DNA fragmentation and MDA level (P<0.05).Conclusion: Adding curcumin and melatonin in combination to the freezing environment will have a positive effect on sperm parameters after freezing.